The Role of Dividend Policy as Mediating the Effect of Leverage and Profitability on Stock Prices in Food and Beverage Subsector Companies Listed on the Indonesian Stock Exchange - Erwan Sastrawan Farid; Haeruddin Tobigo; Ayu Putri Utami; Nini Andriani; Rian Risendy; Leni Karlina; Moh. Agus; Siti Nurhasanah Yusuf (Universitas Muhammadiyah Palu, 2025)
Stock price fluctuations are a common phenomenon in the capital market. One of the internal factors that affect stock price fluctuations is the company's dividend distribution decision. Dividends distributed to shareholders can affect investors' perceptions of the company's value and share price. In determining the amount of dividends to be distributed, companies need to consider several factors such as leverage ratio, liquidity ratio, and profitability. The leverage ratio describes the extent to which the company uses borrowed funds. The use of high leverage can limit the company's ability to pay dividends. Conversely, low leverage provides greater financial flexibility to pay higher or consistent dividends. Leverage has a significant effect on stock price fluctuations. Companies with high leverage tend to be more risky for investors due to large interest obligations. As a result, their share prices are more volatile than companies with low leverage. In addition, high profitability indicates the company's ability to generate large profits. This allows the company to pay dividends more consistently or in large amounts. Conversely, low profitability may lead to withholding dividend payments. High profitability also supports stock price stability as it attracts investors. So it is necessary to analyse the effect of financial ratios and dividend policy on stock price volatility of food and beverage companies.